Puasa Selama Kebuntingan terhadap jumlah sel neuron Cereberum dan Cerebellum Rattus norvegicus Baru Lahir - Ucik Nurul Hidayati; Hermanto Tri Joewono; Muhammad Miftahussurur; Agus Sulistyono; Martono Tri Utomo; Sulistiawati Sulistiawati (Universitas Wijaya Kusuma Surabaya, 2020)
Fasting by pregnant women causes increasing neurons in the brain. An increasing number of neuron cells will speed up information processing, so it is expected to increasing intelligence. The purpose of this study was to analyze the effect of fasting during pregnancy on the number of new cells of the cerebrum neuron and the newly born Rattus norvegicus cerebellum. The research design was true experimental laboratory posttest only with control group design. Pregnant Rattus norvegicus samples consisted of 3 groups and 1 control group with a total sample of 32 divided by 4; Xo control group without fast treatment, fasting X1 group in 1st trimester (2 days), fasting X2 group in 2nd trimester (2 days), fasting group X3 at TM 3 (2 days). Data analysis using Shapiro – Wilk normality test, followed by ANOVA test and using SPSS for Windows 23 software. The results of statistical analysis showed no significant difference in the number of cerebrum neuron cells in the four groups P = 0.210 (p> 0.05) and there were significant differences in the number of cerebrum neuron cells in the four groups P = 0.032 (p <0.05). The conclusion of this study is there was no difference in the number of neuron cells in cerebrum and cerebellum of Rattus norvegicus newborn in the fasting mother 2 days during trimester I, II dan III of pregnancy. There was a difference in the number of neuron cells in the new cerebellum of Rattus norvegicus fasting for 2 days during trimester III of pregnancy, and there were differences the effect of the number of neuron cell in cerebellum of Rattus norvegicus in all groups.